Increasing soak time improves size selection and harvesting patterns in common whelk (Buccinum undatum) pot fisheries - Moritz Eichert; Bent Herrmann; Michel J. Kaiser; Jure Brčić (Reviews in Fish Biology and Fisheries, 2026)
Common whelk is a neo-gastropod that is intensively fished on the west and east temperate Atlantic with baited pots. The UK hosts the largest Whelk fishery contributing 10–15% to the national Shellfish landings, worth 15–27 million £ a year. The fishery is regulated by a minimum conservation reference size (MCRS) which for most areas is set at 45 mm total shell length. However, scientific information quantifying the size selectivity for pots to catch common whelk and to what extent soak time applied affects it is limited leaving it unknown to what extent the existing fishing practice obtains a size selection that matches the MCRS. Therefore, experimental fishing trials were conducted to fill this knowledge gap. The results obtained demonstrated that soak time significantly affected the size selectivity for the pots. Specifically, it was found that only 75% of the whelks would be size sorted if soaking time for the pots was as short as 18h while with an extended soaking time to 46h practically all (97%) whelks entering were size selected by the escape gaps in the pots. Therefore, soaking time needs to be considered to obtain an efficient size selection at the seabed.

Hook modification to reduce rockfish and Pacific spiny dogfish bycatch in the U.S. West Coast Pacific halibut longline fishery - Dylan S. Heppell; Mark J. M. Lomeli; W. Waldo Wakefield; Bent Herrmann; Claude L. Dykstra; Ian J. Stewart (Reviews in Fish Biology and Fisheries, 2026)

Chimpanzees steal less from their friends and expect them to do the same - Oded Ritov; Christoph J. Völter; Liran Samuni; Avi Benozio; Dacher Keltner; Jan M. Engelmann; Laura S. Lewis; Esther Herrmann (Evolution and Human Behavior, 2026)

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

Long-term P management has limited impacts on soil microbial communities, with unique patterns driven by location, land use, and soil depth - Kirill Bogdanov; Parag Bhople; Giulia Bondi; Naoise Nunan; Lars Elsgaard; Anke M. Herrmann; Karl G. Richards; Mart Ros; David Wall; Fiona Brennan; Sergio E. Morales; Timothy J. Clough (Applied Soil Ecology, 2026)

Beyond mobility: A prospective study on diet and metabolism in hereditary spastic paraplegia - Christina Erhardt; Imke T. Spatz; Hans J. Herrmann; Zacharias Kohl; Yurdagül Zopf; Heiko Gassner; Jürgen Winkler; Martin Regensburger (Metabolic Brain Disease, 2026)
Metabolism plays an important role in neurodegenerative diseases. Hereditary spastic paraplegias (HSP) are a heterogeneous group of rare genetic neurodegenerative disorders, commonly characterized by the clinical syndrome of progressive lower limb spasticity and mobility loss. Obesity has been linked to distinct genotypes, but the role of metabolism and nutrition in HSP remains unclear.We aimed to To evaluate metabolism and nutrition in specific HSP genotypes and to assess the impact of nutritional counseling on disease progression and body composition. In this prospective explorative pilot study, we assessed the neurological, metabolic and nutritional status of patients with HSP at baseline and one year after nutritional counseling. A total of 36 patients with genetically confirmed SPG4-, SPG7- and SPG11-associated HSP were recruited. BMI in SPG4 and SPG7 was comparable to healthy population data, whereas SPG11 showed significantly higher BMI (+ 22.9%, p < 0.05) with a considerable interindividual variability. Across all genotypes, disease severity according to the Spastic Paraplegia Rating Scale correlated negatively with leg muscle mass (ρ = -0.39, p < 0.05), protein (ρ = -0.35, p < 0.05) and fiber intake (ρ = -0.41, p < 0.05). After one year, there was a significant loss of relative muscle mass (-7.2%, p < 0.001). Progressive loss of muscle mass in HSP asks for an effective nutritional intervention combined with exercise in order to influence disease progression in HSP. The SPG11-associated obese phenotype may evolve with disease progression due to multifactorial metabolic changes, beyond reduced mobility.

Tunable electrochemical hydrogen evolution reaction employing surface acoustic waves - Michael J. Saule; Sixuan Wang; Rudolf Herrmann; Elmar Mitterreiter; Achim Wixforth; Ursula Wurstbauer; Christoph Westerhausen (Fuel, 2026)

Harnessing Sentinel-2 imagery and AgERA5 data using Google Earth Engine for developing chickpea mechanistic growth modeling and pre-harvest empirical yield forecast - Omer Perach; Roy Sadeh; Asaf Avneri; Neta Solomon; David J. Bonfil; Or Ram; Harel Greenblatt; Ran N. Lati; Ittai Herrmann (Precision Agriculture, 2025)
Precision Agriculture (PA) adoption by farmers is limited by costs and technological complexity. Google Earth Engine (GEE) is used in large-scale crop research but remains underutilized for PA applications. Crop yield variability is widely studied, yet research advancements increasingly widen the gap to practical use. To address this, a GEE platform was established, harnessing Sentinel-2 and AgERA5 for chickpea mechanistic daily simulation of the Total Above-Ground Dry Biomass (TAGDB) and Grain Dry Biomass (GDB). In addition, Sentinel-2 spectral reflectance was used to train an empirical Random Forest (RF) model on GEE to forecast Grain Yield (GY) two months prior to harvest. Both mechanistic and empirical models were evaluated at field scale using GY data from 68 fields (2021–2024), including sub-field evaluation from eight fields. The mechanistic and empirical RF models achieved sub-field GY performance with a coefficient of determination (R²), root mean square error (RMSE), and relative RMSE of 0.49, 1.49 t ha⁻¹, and 19.89%, and 0.24, 1.15 t ha⁻¹, and 15.35%, respectively. At the field scale, the mechanistic model resulted in 0.43, 0.9 t ha⁻¹, and 19.35%, while the RF model achieved 0.37, 0.83 t ha⁻¹, and 17.85%, respectively. The models performed similarly to studies in other crops but with a key advantage - they can be fully executed within GEE. A companion app was built to support both the mechanistic and empirical models within GEE. Chickpea farmers can use the mechanistic model to examine the spatial progression of TAGDB and GDB, both retrospectively and in a near real time manner. The RF forecast model can then be used to anticipate GY variability prior to harvest. The streamlined design of the mechanistic model, together with the empirical model implemented in GEE and the open-source scripts available on GitHub, supports efficient adaptation to additional crops.

Resistively heated spiral wound module for temperature swing adsorption of CO2 - Carla Esch; Marlon Mehltretter; Johannes Neese; Stefan Herrmann; Roman Ryapushkin; Christian J. Linnartz; Matthias Wessling (Chemical Engineering Journal, 2025)

Ecosystem Metabolic Rates Estimated from Diel Oxygen Measurements in Two Subtropical Estuaries - J. M. Arriola; R. G. Najjar; H. Briceño; C. Hu; M. Herrmann; M. W. Beck (Estuaries and Coasts, 2025)
Subtropical estuaries worldwide are facing increasing pressure from human population growth, development, and climate change. Carbon is a useful currency for understanding how estuaries respond to these pressures and yet relatively little is known about carbon cycling in subtropical estuaries. Here we compute gross primary production (GPP), ecosystem respiration (ER), and net ecosystem production (NEP) from the diurnal cycle in dissolved oxygen measured during 38 week-long individual deployments over three years in two estuaries in the southeastern United States, Biscayne Bay and Tampa Bay. On average for both estuaries, GPP and ER nearly balance, with NEP about an order of magnitude smaller. Even though production in Tampa Bay and Biscayne Bay is dominated by different primary producers and limiting nutrients, mean GPP was the same, about 190 mmol O 2 m –2 d –1 (570 g C m –2 y –1 ). Our GPP estimates for Biscayne Bay are more than an order of magnitude greater than the only other productivity estimates available for this system, which are planktonic net primary productivity measurements from the late 1970s. GPP was strongly correlated with water temperature in Biscayne Bay ( r = 0.60) but had the strongest correlation with salinity in Tampa Bay ( r = 0.39). These findings highlight the importance of more frequent production measurements in these complex estuaries, especially in the face of a changing climate.

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

Hard-seeded annual pasture legume phases are a profitable and low risk option in mixed farming regions with low to medium rainfall - Dean T. Thomas; Sadeeka L. Jayasinghe; Chris Herrmann; Robert J. Harrison; Bonnie M. Flohr; Roger A. Lawes (Agricultural Systems, 2025)

Salix species and varieties affect the molecular composition and diversity of soil organic matter - Louis J. P. Dufour; Johanna Wetterlind; Naoise Nunan; Katell Quenea; Andong Shi; Martin Weih; Anke M. Herrmann (Plant and Soil, 2025)
Background and aims Most studies of the relationships between the composition of soil organic matter and plant cover have been carried out at the plant genera level. However, they have largely overlooked the potential effects that plant varieties, belonging to the same genus, can have on soil organic matter. Methods We investigated whether plant varieties belonging to different Salix species ( S. dasyclados and S. viminalis) impacted the composition of organic matter using mid-infrared spectroscopy and pyrolysis GC/MS. Top-soils were taken from an 18 year-old long-term field trial where six Salix varieties were grown as short-rotation coppice under two fertilisation regimes. Results Significant differences in the molecular composition and diversity of the soil organic matter were observed in the fertilised plots. The effects were mostly visible at the species level, i.e. the organic matter in soil under S. dasyclados varieties had higher molecular diversity and lignin content than under S. viminalis , potentially due to differences in the amount and composition of their litter inputs. Smaller differences among varieties from the same species were also observed. No significant effects of Salix varieties were observed in the unfertilised plots. The relatively high degree of spatial variability of several soil properties found in these plots may have masked plant variety and/or species effects. Conclusion This study provides evidence that the identity of Salix species or varieties can affect the molecular composition and diversity of soil organic matter. The corresponding traits should be considered in breeding programmes to enhance soil organic C accumulation and persistence.

River discharge - tide interactions and tide propagation in the mesotidal tropical estuary of the Van Uc river, Red River delta, Vietnam - J. Pénicaud; M. Herrmann; F. Toublanc; V.D. Vinh; S. Ouillon (Regional Studies in Marine Science, 2025)

Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

The seasonal variation of Asian dust, anthropogenic PM, and their sources in Dushanbe, Tajikistan - Khanneh Wadinga Fomba; Oluwabamise Lekan Faboya; Nabil Deabji; Abduvosit Makhmudov; Julian Hofer; Eduardo J. dos Santos Souza; Konrad Müller; Dietrich Althausen; Safarali Sharipov; Sabur Abdullaev; Hartmut Herrmann (Atmospheric Environment, 2024)

The influence of long-range transported Saharan dust on the inflammatory potency of ambient PM2.5 and PM10 - Gerrit Bredeck; Eduardo J. dos S. Souza; Claudia Wigmann; Khanneh Wadinga Fomba; Hartmut Herrmann; Roel P.F. Schins (Environmental Research, 2024)

Correction to: Chickpea leaf water potential estimation from ground and VENµS satellite - Roy Sadeh; Asaf Avneri; Yaniv Tubul; Ran N. Lati; David J. Bonfil; Zvi Peleg; Ittai Herrmann (Precision Agriculture, 2024)

Chickpea leaf water potential estimation from ground and VENµS satellite - Roy Sadeh; Asaf Avneri; Yaniv Tubul; Ran N. Lati; David J. Bonfil; Zvi Peleg; Ittai Herrmann (Precision Agriculture, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Optimization of chickpea irrigation in a semi-arid climate based on morpho-physiological parameters - Asaf Avneri; Zvi Peleg; David J. Bonfil; Roy Sadeh; Omer Perach; Ittai Herrmann; Shahal Abbo; Ran N. Lati (European Journal of Agronomy, 2024)

In-vitro method and model to estimate methane emissions from liquid manure management on pig and dairy farms in four countries - Søren O. Petersen; Chun Ma; Julio E. Hilgert; Kristina Mjöfors; Paria Sefeedpari; Barbara Amon; André Aarnink; Balázs Francó; Federico Dragoni; Karin Groenestein; Steen Gyldenkærne; Christiane Herrmann; et al. (Journal of Environmental Management, 2024)

From Diverse Perspectives to Unified Strategies: European University Alliances and the Development of Adaptable Science Communication Concepts - Vanessa J. Herrmann; Annabell Heimer; Inga-Maria Eichentopf; Gunter Süß (BHM Berg- und Hüttenmännische Monatshefte, 2024)
Communicating scientific subjects to non-academic, non-specialist, or very young audiences using various event formats (lecture series, panel discussions, science slams, Children’s Universities, Citizen Universities, etc.) is a key aspect of science communication. In the EURECA-PRO University Alliance, the implementation of these kinds of formats will be given greater focus at all institutions to make significant topics accessible in ways that go beyond the institutional walls of the universities. To this end, approaches are being developed and tested to identify and reduce existing hurdles for the public. At the same time, in an international structure such as EURECA-PRO, it is essential to know individual frameworks to ensure that measures promoting a uniform strategy can be implemented by everyone. In order to develop adaptable strategies for universities with different thematic focuses and locations in Europe, certain conditions for success must be identified and considered. In addition to the needs and resources of target groups, the requirements, and opportunities of the universities—as dictated by their respective circumstances—must also be considered. Using the examples of the EURECA-PRO partners Technical University of Crete in Chania (TUC), Silesian University of Technology in Gliwice (SUT), and Montanuniversität Leoben (MUL), challenges and results will be discussed.

Carbon and hydrogen isotope fractionation of phthalates during photocatalysis reactions in aqueous solution containing Fe(III) complexes or iron minerals - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Oliver J. Lechtenfeld; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2023)

A genomic test of subspecies in the Eunota togata species group (Coleoptera: Cicindelidae): Morphology masks evolutionary relationships and taxonomy - Robert A. Laroche; Daniel P. Duran; Cin-Ty A. Lee; William Godwin; Stephen J. Roman; David P. Herrmann; Scott P. Egan (Molecular Phylogenetics and Evolution, 2023)

Model-parallel Fourier neural operators as learned surrogates for large-scale parametric PDEs - Thomas J. Grady; Rishi Khan; Mathias Louboutin; Ziyi Yin; Philipp A. Witte; Ranveer Chandra; Russell J. Hewett; Felix J. Herrmann (Computers & Geosciences, 2023)

Testing of hook sizes and appendages to reduce yelloweye rockfish bycatch in a Pacific halibut longline fishery - Mark J.M. Lomeli; W. Waldo Wakefield; Meagan Abele; Claude L. Dykstra; Bent Herrmann; Ian J. Stewart; Gregory C. Christie (Ocean & Coastal Management, 2023)

UAS-based imaging for prediction of chickpea crop biophysical parameters and yield - Asaf Avneri; Shlomi Aharon; Anna Brook; Guy Atsmon; Evgeny Smirnov; Roy Sadeh; Shahal Abbo; Zvi Peleg; Ittai Herrmann; David J. Bonfil; Ran Nisim Lati (Computers and Electronics in Agriculture, 2023)

Impacts on biodiversity from codend and fisher selection in bottom trawl fishing - Chryssi Mytilineou; Bent Herrmann; Christopher J. Smith; Danai Mantopoulou-Palouka; Aikaterini Anastasopoulou; Apostolos Siapatis; Antonello Sala; Persefoni Megalofonou; Nadia Papadopoulou; Vassiliki Vassilopoulou; Caterina Stamouli; Stefanos Kavadas; et al. (Frontiers in Marine Science, 2022)
Fisheries have important impacts on marine biodiversity. In this work, combined information on the abundance, species richness, diversity indices, species composition, trophic level and vulnerability index were examined for the first-time to detect differences in five units related to trawl fishing: the fish assemblage entering the trawl codend, and the escaping, retained, discarded and landed fractions, derived by the gear and fisher selection practices. The work was based on a case study conducted in the Mediterranean Sea, using three different meshes in the trawl codend (40mm-40D and 50mm-50D diamond meshes, and 40 mm-40S square meshes) and a cover of the codends with small mesh size. In general, trawl fishing produces an escaping fraction that was always lower in abundance, richness, and vulnerability index, similar in diversity indices and trophic level, and different in species composition compared to the fish assemblage entering the codend. In almost all cases, fishers selected as landings a fraction that was the lowest in diversity indices, and the highest in trophic level. In contrast, fishers discarded a fraction that was the highest in diversity and vulnerability index, and the lowest in trophic level. Although the three codends did not differ significantly in the fraction of escapees in terms of diversity indices, trophic level, and vulnerability index, the 40S codend showed a significantly higher percentage in the escaping number of species and individuals, and less differences in the species composition; in addition, lower percentage in abundance of discards and higher of landings in the retained catch (0.6:1) than did the other two codends (0.9:1). It was suggested that an urgent modification of the trawl for the elimination of the discarded highly vulnerable species (e.g. Elasmobranchs) is needed, and that trawl species-selectivity should be improved by allowing escape or avoiding catch of the discarded fraction to minimize biodiversity losses.

Simulation of steam/air leakage through small-scale cracked concrete specimen - L. Bahr; J. Sievers; M. Zemann; N. Herrmann (European Journal of Environmental and Civil Engineering, 2022)

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Evaluation of biotransformation capacity of transplastomic plants and hairy roots of Nicotiana tabacum expressing human cytochrome P450 2D6 - Y. V. Sheludko; I. M. Gerasymenko; F. J. Herrmann; H. Warzecha (Transgenic Research, 2022)
Cytochrome P450 monooxygenases (CYPs) are important tools for regio- and stereoselective oxidation of target molecules or engineering of metabolic pathways. Functional heterologous expression of eukaryotic CYPs is often problematic due to their dependency on the specific redox partner and the necessity of correct association with the membranes for displaying enzymatic activity. Plant hosts offer advantages of accessibility of reducing partners and a choice of membranes to insert heterologous CYPs. For the evaluation of plant systems for efficient CYP expression, we established transplastomic plants and hairy root cultures of Nicotiana tabacum carrying the gene encoding human CYP2D6 with broad substrate specificity. The levels of CYP2D6 transcript accumulation and enzymatic activity were estimated and compared with the data of CYP2D6 transient expression in N. benthamiana . The relative level of CYP2D6 transcripts in transplastomic plants was 2–3 orders of magnitude higher of that observed after constitutive or transient expression from the nucleus. CYP2D6 expressed in chloroplasts converted exogenous synthetic substrate loratadine without the need for co-expression of the cognate CYP reductase. The loratadine conversion rate in transplastomic plants was comparable to that in N. benthamiana plants transiently expressing a chloroplast targeted CYP2D6 from the nucleus, but was lower than the value reported for transiently expressed CYP2D6 with the native endoplasmic reticulum signal-anchor sequence. Hairy roots showed the lowest substrate conversion rate, but demonstrated the ability to release the product into the culture medium. The obtained results illustrate the potential of plant-based expression systems for exploiting the enzymatic activities of eukaryotic CYPs with broad substrate specificities.

Biohydrogen Production from Agro-industrial Wastes Using Clostridium beijerinckii and Isolated Bacteria as Inoculum - Walter J. Martinez-Burgos; Jair Rosário do Nascimento Junior; Adriane Bianchi Pedroni Medeiros; Leonardo Wedderhoff Herrmann; Eduardo Bittencourt Sydney; Carlos Ricardo Soccol (BioEnergy Research, 2022)

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Parasites of chinstrap penguins (Pygoscelis antarctica) from three localities in the Antarctic Peninsula and a review of their parasitic fauna - Daniel A. González-Acuña; Lucila Moreno; Michelle Wille; Bjorn Herrmann; Mike J. Kinsella; Ricardo L. Palma (Polar Biology, 2021)

Nematode biphasic ‘boom and bust’ dynamics are dependent on host bacterial load while linking dauer and mouth‐form polyphenisms - Tess Renahan; Wen‐Sui Lo; Michael S. Werner; Jacques Rochat; Matthias Herrmann; Ralf J. Sommer (Environmental Microbiology, 2021)
Cross‐kingdom interactions involve dynamic processes that shape terrestrial ecosystems and represent striking examples of co‐evolution. The multifaceted relationships of entomopathogenic nematodes with their insect hosts and symbiotic bacteria are well‐studied cases of co‐evolution and pathogenicity. In contrast, microbial interactions in soil after the natural death of insects and other invertebrates are minimally understood. In particular, the turnover and succession of nematodes and bacteria during insect decay have not been well documented ‐ although it represents a rich ecological niche with multiple species interactions. Here, we utilize developmentally plastic nematode Pristionchus pacificus and its associated scarab beetles as models. On La Réunion Island, we collected rhinoceros beetle Oryctes borbonicus , induced death, and placed carcasses in cages both on the island and in a mock‐natural environment in the laboratory controlling for high spatial and temporal resolution. Investigating nematode population density and dispersal dynamics, we were able to connect two imperative plasticities, dauer and mouth form. We observed a biphasic ‘boom and bust’ dispersal dynamic of dauer larvae that corresponds to bacterial load on carcasses but not bacterial type. Strikingly, all post‐dauer adults have the predatory mouth form, demonstrating novel intricate interactions on decaying insect hosts. Thus, ecologically relevant survival strategies incorporate critical plastic traits.

Global patterns of forest autotrophic carbon fluxes - Rebecca Banbury Morgan; Valentine Herrmann; Norbert Kunert; Ben Bond‐Lamberty; Helene C. Muller‐Landau; Kristina J. Anderson‐Teixeira (Global Change Biology, 2021)
Carbon (C) fixation, allocation, and metabolism by trees set the basis for energy and material flows in forest ecosystems and define their interactions with Earth's changing climate. However, while many studies have considered variation in productivity with latitude and climate, we lack a cohesive synthesis on how forest carbon fluxes vary globally with respect to climate and one another. Here, we draw upon 1,319 records from the Global Forest Carbon Database, representing all major forest types and the nine most significant autotrophic carbon fluxes, to comprehensively review how annual C cycling in mature, undisturbed forests varies with latitude and climate on a global scale. Across all flux variables analyzed, rates of C cycling decreased continuously with absolute latitude—a finding that confirms multiple previous studies and contradicts the idea that net primary productivity of temperate forests rivals that of tropical forests. C flux variables generally displayed similar trends across latitude and multiple climate variables, with no differences in allocation detected at this global scale. Temperature variables in general, and mean annual temperature or temperature seasonality in particular, were the best single predictors of C flux, explaining 19%–71% of variation in the C fluxes analyzed. The effects of temperature were modified by moisture availability, with C flux reduced under hot and dry conditions and sometimes under very high precipitation. Annual C fluxes increased with growing season length and were also influenced by growing season climate. These findings clarify how forest C flux varies with latitude and climate on a global scale. In an era when forests will play a critical yet uncertain role in shaping Earth's rapidly changing climate, our synthesis provides a foundation for understanding global patterns in forest C cycling.

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

Human exposure to synthetic endocrine disrupting chemicals (S-EDCs) is generally negligible as compared to natural compounds with higher or comparable endocrine activity: how to evaluate the risk of the S-EDCs? - Herman Autrup; Frank A. Barile; Sir Colin Berry; Bas J. Blaauboer; Alan Boobis; Herrmann Bolt; Christopher J. Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2020)
Theoretically, both synthetic endocrine disrupting chemicals (S-EDCs) and natural (exogenous and endogenous) endocrine disrupting chemicals (N-EDCs) can interact with endocrine receptors and disturb hormonal balance. However, compared to endogenous hormones, S-EDCs are only weak partial agonists with receptor affinities several orders of magnitude lower. Thus, to elicit observable effects, S-EDCs require considerably higher concentrations to attain sufficient receptor occupancy or to displace natural hormones and other endogenous ligands. Significant exposures to exogenous N-EDCs may result from ingestion of foods such as soy-based diets, green tea and sweet mustard. While their potencies are lower as compared to natural endogenous hormones, they usually are considerably more potent than S-EDCs. Effects of exogenous N-EDCs on the endocrine system were observed at high dietary intakes. A causal relation between their mechanism of action and these effects is established and biologically plausible. In contrast, the assumption that the much lower human exposures to S-EDCs may induce observable endocrine effects is not plausible. Hence, it is not surprising that epidemiological studies searching for an association between S-EDC exposure and health effects have failed. Regarding testing for potential endocrine effects, a scientifically justified screen should use in vitro tests to compare potencies of S-EDCs with those of reference N-EDCs. When the potency of the S-EDC is similar or smaller than that of the N-EDC, further testing in laboratory animals and regulatory consequences are not warranted.

Differential Bioaccumulation of Mercury and Selenium in Stomach Contents and Tissues of Three Colorado, USA, Cutthroat Trout Populations - Scott J. Herrmann; Del Wayne R. Nimmo; James S. Carsella; Igor V. Melnykov; Christopher M. Kennedy; Kevin B. Rogers; Lynn M. Herrmann-Hoesing (Bulletin of Environmental Contamination and Toxicology, 2020)

Combining selection models and population structures to inform fisheries management: a case study on hake in the Mediterranean bottom trawl fishery - CHRYSSI MYTILINEOU; BENT HERRMANN; STEFANOS KAVADAS; CHRIS J. SMITH; PERSEFONI MEGALOFONOU (Mediterranean Marine Science, 2020)
The reduction of juvenile catch and discards are important targets in fisheries policy. This work examines how selection models can predict the size structure (LFD) of discards and landings considering the effects of area, time period, gear and fisher behaviour. Additional exploitation indicators related to the gear used, fisher's selection pattern, and discards were also estimated. The approach is demonstrated in a study concerning hake in the Mediterranean trawl fishery, focusing on high (HRA) and low (LRA) recruitment areas in the Saronikos Gulf (Eastern Mediterranean) during two periods (June, September) using two codends (40 mm square-40S, 50 mm diamond-50D mesh). The predicted discards LFDs revealed generally higher percentages in the HRA in June when using the 50D. The predicted landings LFDs showed higher percentages in the LRA in September for both codends, but undersized hake were always included. LFDs and exploitation indicators indicated that both codends were inappropriate for sustainable fishing of hake in the HRA, where 50D performed worse than the 40S. Fishing with both codends in the LRA in September revealed the lowest discards rates and minimum sizes of landings close to MCRS (minimum conservation reference size). These results can provide information to fisheries management aiming to protect juveniles and reduce discards through spatio-temporal fishing closures.

Deformation Experiments on Bowland and Posidonia Shale—Part II: Creep Behavior at In Situ pc–T Conditions - J. Herrmann; E. Rybacki; H. Sone; G. Dresen (Rock Mechanics and Rock Engineering, 2020)

Genome‐inferred spatio‐temporal resolution of an uncultivated Roizmanbacterium reveals its ecological preferences in groundwater - Patricia Geesink; Carl‐Eric Wegner; Alexander J. Probst; Martina Herrmann; Hang T. Dam; Anne‐Kristin Kaster; Kirsten Küsel (Environmental Microbiology, 2020)
Summary Subsurface ecosystems like groundwater harbour diverse microbial communities, including small‐sized, putatively symbiotic organisms of the Candidate Phyla Radiation, yet little is known about their ecological preferences and potential microbial partners. Here, we investigated a member of the superphylum Microgenomates ( Cand . Roizmanbacterium ADI133) from oligotrophic groundwater using mini‐metagenomics and monitored its spatio‐temporal distribution using 16S rRNA gene analyses. A Roizmanbacteria‐specific quantitative PCR assay allowed us to track its abundance over the course of 1 year within eight groundwater wells along a 5.4 km hillslope transect, where Roizmanbacteria reached maximum relative abundances of 2.3%. In‐depth genomic analyses suggested that Cand . Roizmanbacterium ADI133 is a lactic acid fermenter, potentially able to utilize a range of complex carbon substrates, including cellulose. We hypothesize that it attaches to host cells using a trimeric autotransporter adhesin and inhibits their cell wall biosynthesis using a toxin–antitoxin system. Network analyses based on correlating Cand . Roizmanbacterium ADI133 abundances with amplicon sequencing‐derived microbial community profiles suggested one potential host organism, classified as a member of the class Thermodesulfovibrionia (Nitrospirae). By providing lactate as an electron donor Cand . Roizmanbacterium ADI133 potentially mediates the transfer of carbon to other microorganisms and thereby is an important connector in the microbial community.

The nature and origin of pigments in black opal from Lightning Ridge, New South Wales, Australia - J. R. Herrmann; R. Maas; P. F. Rey; S. P. Best (Australian Journal of Earth Sciences, 2019)

Soluble Epoxide Hydrolase-Derived Linoleic Acid Oxylipins in Serum Are Associated with Periventricular White Matter Hyperintensities and Vascular Cognitive Impairment - Di Yu; Marie Hennebelle; Demetrios J. Sahlas; Joel Ramirez; Fuqiang Gao; Mario Masellis; Hugo Cogo-Moreira; Richard H. Swartz; Nathan Herrmann; Pak Cheung Chan; Jacqueline A. Pettersen; Donald T. Stuss; et al. (Translational Stroke Research, 2019)

Enabling numerically exact local solver for waveform inversion—a low-rank approach - Rajiv Kumar; Bram Willemsen; Felix J. Herrmann; Alison Malcolm (Computational Geosciences, 2019)

Seasonal and Interannual Variability in Net Ecosystem Production of a Subtropical Coastal Lagoon Inferred from Monthly Oxygen Surveys - Lauren E. Seidensticker; Raymond G. Najjar; Maria Herrmann; Joseph N. Boyer; Henry O. Briceño; W. Michael Kemp; Daniel J. Tomaso (Estuaries and Coasts, 2019)

Reduced spontaneous low frequency oscillations as measured with functional near-infrared spectroscopy in mild cognitive impairment - Julia B. M. Zeller; Andrea Katzorke; Laura D. Müller; Judith Breunig; Florian B. Haeussinger; Jürgen Deckert; Bodo Warrings; Martin Lauer; Thomas Polak; Martin J. Herrmann (Brain Imaging and Behavior, 2019)

Deformation Experiments on Bowland and Posidonia Shale—Part I: Strength and Young’s Modulus at Ambient and In Situ pc–T Conditions - J. Herrmann; E. Rybacki; H. Sone; G. Dresen (Rock Mechanics and Rock Engineering, 2018)

Protective potential of dimethyl fumarate in a mouse model of thalamocortical demyelination - Manuela Cerina; Venu Narayanan; Anna Delank; Patrick Meuth; Stephanie Graebenitz; Kerstin Göbel; Alexander M. Herrmann; Stefanie Albrecht; Thiemo Daldrup; Thomas Seidenbecher; Ali Gorji; Tanja Kuhlmann; et al. (Brain Structure and Function, 2018)

ScalA-FS: expert-based ex-ante assessments of local requirements and success potential of upgrading strategies for improving food security in rural Tanzania - Götz Uckert; Frieder Graef; Anja Faße; Ludger Herrmann; Harry Hoffmann; Frederick C. Kahimba; Luitfred Kissoly; Hannes J. König; Christine Lambert; Henry Mahoo; Bashir Makoko; Leon Mrosso; et al. (Food Security, 2018)

ForC: a global database of forest carbon stocks and fluxes - Kristina J. Anderson‐Teixeira; Maria M. H. Wang; Jennifer C. McGarvey; Valentine Herrmann; Alan J. Tepley; Ben Bond‐Lamberty; David S. LeBauer (Ecology, 2018)
Forests play an influential role in the global carbon (C) cycle, storing roughly half of terrestrial C and annually exchanging with the atmosphere more than five times the carbon dioxide ( CO 2 ) emitted by anthropogenic activities. Yet, scaling up from field‐based measurements of forest C stocks and fluxes to understand global scale C cycling and its climate sensitivity remains an important challenge. Tens of thousands of forest C measurements have been made, but these data have yet to be integrated into a single database that makes them accessible for integrated analyses. Here we present an open‐access global Forest Carbon database (ForC) containing previously published records of field‐based measurements of ecosystem‐level C stocks and annual fluxes, along with disturbance history and methodological information. ForC expands upon the previously published tropical portion of this database, TropForC ( https://doi.org/10.5061/dryad.t516f ), now including 17,367 records (previously 3,568) representing 2,731 plots (previously 845) in 826 geographically distinct areas. The database covers all forested biogeographic and climate zones, represents forest stands of all ages, and currently includes data collected between 1934 and 2015. We expect that ForC will prove useful for macroecological analyses of forest C cycling, for evaluation of model predictions or remote sensing products, for quantifying the contribution of forests to the global C cycle, and for supporting international efforts to inventory forest carbon and greenhouse gas exchange. A dynamic version of ForC is maintained at on GitHub ( https://GitHub.com/forc-db ) , and we encourage the research community to collaborate in updating, correcting, expanding, and utilizing this database. ForC is an open access database, and we encourage use of the data for scientific research and education purposes. Data may not be used for commercial purposes without written permission of the database PI . Any publications using ForC data should cite this publication and Anderson‐Teixeira et al. (2016a) (see Metadata S1 ). No other copyright or cost restrictions are associated with the use of this data set.

Effect of fish length and nutritional condition on the fecundity of distressed Atlantic cod Gadus morhua from the Baltic Sea - M. Mion; A. Thorsen; F. Vitale; J. Dierking; J. P. Herrmann; B. Huwer; B. von Dewitz; M. Casini (Journal of Fish Biology, 2018)
The disappearance of larger individuals and the decrease in individual body condition suffered by Atlantic cod Gadus morhua in the eastern Baltic during the past two decades can be expected to affect the stock reproductive output. To investigate this, female G. morhua were collected during the spawning and pre‐spawning period in 2015−2016. The current individual potential fecundity ( F P ) of eastern Baltic G. morhua was estimated and analysed in relation to total length ( L T ) and indices of nutritional status such as body condition ( K ) and hepato‐somatic index ( I H ) using generalized linear models. In addition, the current prevalence of atresia and its potential relation to K were investigated. Moreover, a calibration curve to estimate F P from oocyte diameter, based on the autodiametric oocyte counting method, was established for the first time for eastern Baltic G. morhua and can be used for future fecundity studies on this stock. The results showed that F P was mainly positively related to fish length, but K and I H also contributed significantly to the variation in F P . The model predicted that fish with K = 1·2 have a F P 51% higher than fish of the same L T with K = 0·8. The prevalence of fecundity regulation by atresia was 5·8%, but it was found only in fish in the pre‐spawning maturity stage and with low K . Temporal changes in biological features such as the length composition and individual body condition of eastern Baltic G. morhua , should be accounted for when estimating stock reproductive potential.

Tomographic Study of Internal Erosion of Particle Flows in Porous Media - Filippo Bianchi; Falk K. Wittel; Marcel Thielmann; Pavel Trtik; Hans J. Herrmann (Transport in Porous Media, 2018)

Changes in motor performance and mental workload during practice of reaching movements: a team dynamics perspective - Isabelle M. Shuggi; Patricia A. Shewokis; Jeffrey W. Herrmann; Rodolphe J. Gentili (Experimental Brain Research, 2018)

Creep of Posidonia Shale at Elevated Pressure and Temperature - E. Rybacki; J. Herrmann; R. Wirth; G. Dresen (Rock Mechanics and Rock Engineering, 2017)

Prolonged suppressive antibiotic therapy for prosthetic joint infection in the elderly: a national multicentre cohort study - V. Prendki; T. Ferry; P. Sergent; E. Oziol; E. Forestier; T. Fraisse; S. Tounes; S. Ansart; J. Gaillat; S. Bayle; O. Ruyer; F. Borlot; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Field studies measuring the aerosolization of endotoxin during the land application of Class B biosolids - R. F. Herrmann; R. J. Grosser; D. Farrar; R. B. Brobst (Aerobiologia, 2017)

Peripheral Alterations in Cytokine and Chemokine Levels After Antidepressant Drug Treatment for Major Depressive Disorder: Systematic Review and Meta-Analysis - Cristiano A. Köhler; Thiago H. Freitas; Brendon Stubbs; Michael Maes; Marco Solmi; Nicola Veronese; Nayanna Q. de Andrade; Gerwyn Morris; Brisa S. Fernandes; André R. Brunoni; Nathan Herrmann; Charles L. Raison; et al. (Molecular Neurobiology, 2017)

Prevention of unpredictable chronic stress-related phenomena in zebrafish exposed to bromazepam, fluoxetine and nortriptyline - Matheus Marcon; Ana P. Herrmann; Ricieri Mocelin; Cassiano L. Rambo; Gessi Koakoski; Murilo S. Abreu; Greicy M. M. Conterato; Luiza W. Kist; Maurício R. Bogo; Leila Zanatta; Leonardo J. G. Barcellos; Angelo L. Piato (Psychopharmacology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Connectivity from a different perspective: comparing seed dispersal kernels in connected vs. unfragmented landscapes - John D. Herrmann; Tomás A. Carlo; Lars A. Brudvig; Ellen I. Damschen; Nick M. Haddad; Douglas J. Levey; John L. Orrock; Joshua J. Tewksbury (Ecology, 2016)
Habitat fragmentation can create significant impediments to dispersal. A technique to increase dispersal between otherwise isolated fragments is the use of corridors. Although previous studies have compared dispersal between connected fragments to dispersal between unconnected fragments, it remains unknown how dispersal between fragments connected by a corridor compares to dispersal in unfragmented landscapes. To assess the extent to which corridors can restore dispersal in fragmented landscapes to levels observed in unfragmented landscapes, we employed a stable‐isotope marking technique to track seeds within four unfragmented landscapes and eight experimental landscapes with fragments connected by corridors. We studied two wind‐ and two bird‐dispersed plant species, because previous community‐based research showed that dispersal mode explains how connectivity effects vary among species. We constructed dispersal kernels for these species in unfragmented landscapes and connected fragments by marking seeds in the center of each landscape with 15 N and then recovering marked seeds in seed traps at distances up to 200 m. For the two wind‐dispersed plants, seed dispersal kernels were similar in unfragmented landscapes and connected fragments. In contrast, dispersal kernels of bird‐dispersed seeds were both affected by fragmentation and differed in the direction of the impact: Morella cerifera experienced more and Rhus copallina experienced less long‐distance dispersal in unfragmented than in connected landscapes. These results show that corridors can facilitate dispersal probabilities comparable to those observed in unfragmented landscapes. Although dispersal mode may provide useful broad predictions, we acknowledge that similar species may respond uniquely due to factors such as seasonality and disperser behavior. Our results further indicate that prior work has likely underestimated dispersal distances of wind‐dispersed plants and that factors altering long‐distance dispersal may have a greater impact on the spread of species than previously thought.

Semiautomated quantitative image analysis of glomerular immunohistochemistry markers desmin, vimentin, podocin, synaptopodin and WT-1 in acute and chronic rat kidney disease models - J. Funk; V. Ott; A. Herrmann; W. Rapp; S. Raab; W. Riboulet; A. Vandjour; E. Hainaut; A. Benardeau; T. Singer; B. Jacobsen (Histochemistry and Cell Biology, 2016)

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

Accumulation of Traffic-Related Trace Metals in Urban Winter-Long Roadside Snowbanks - S. Moghadas; K. H. Paus; T. M. Muthanna; I. Herrmann; J. Marsalek; M. Viklander (Water, Air, & Soil Pollution, 2015)

An Overview of the Regional Experiments for Land-atmosphere Exchanges 2012 (REFLEX 2012) Campaign - Wim J. Timmermans; Christiaan van der Tol; Joris Timmermans; Murat Ucer; Xuelong Chen; Luis Alonso; Jose Moreno; Arnaud Carrara; Ramon Lopez; Fernando de la Cruz Tercero; Horacio L. Corcoles; Eduardo de Miguel; et al. (Acta Geophysica, 2015)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

Multilevel impact of the dopamine system on the emotion-potentiated startle reflex - Katharina Domschke; Bernward Winter; Agnieszka Gajewska; Stefan Unterecker; Bodo Warrings; Andrea Dlugos; Swantje Notzon; Kathrin Nienhaus; Falko Markulin; Astrid Gieselmann; Christian Jacob; Martin J. Herrmann; et al. (Psychopharmacology, 2015)

Chemical properties of HULIS from three different environments - T. B. Kristensen; L. Du; Q. T. Nguyen; J. K. Nøjgaard; C. Bender Koch; O. Faurskov Nielsen; A. G. Hallar; D. H. Lowenthal; B. Nekat; D. van Pinxteren; H. Herrmann; M. Glasius; et al. (Journal of Atmospheric Chemistry, 2015)

Ground-level hyperspectral imagery for detecting weeds in wheat fields - I. Herrmann; U. Shapira; S. Kinast; A. Karnieli; D. J. Bonfil (Precision Agriculture, 2013)

Health evaluation of wild gentoo penguins (Pygoscelis papua) in the Antarctic Peninsula - Daniel González-Acuña; Jorge Hernández; Lucila Moreno; Bjorn Herrmann; Ricardo Palma; Alejandra Latorre; Gonzalo Medina-Vogel; Mike J. Kinsella; Nicolas Martín; Karolina Araya; Iván Torres; Nicolás Fernandez; et al. (Polar Biology, 2013)

Field spectroscopy for weed detection in wheat and chickpea fields - Uri Shapira; Ittai Herrmann; Arnon Karnieli; David J. Bonfil (International Journal of Remote Sensing, 2013)

Longitudinal Dispersion Coefficient: Effects of Particle-Size Distribution - Amir Jourak; Vilnis Frishfelds; J. Gunnar I. Hellström; T. Staffan Lundström; Inga Herrmann; Annelie Hedström (Transport in Porous Media, 2013)

Reference ranges and cutoff levels of pneumococcal antibody global serum assays (IgG and IgG2) and specific antibodies in healthy children and adults - M. A. Rose; J. Buess; Y. Ventur; S. Zielen; E. Herrmann; J. Schulze; R. Schubert (Medical Microbiology and Immunology, 2013)

Functional responses of juvenile herring and sprat in relation to different prey types - R. Brachvogel; L. Meskendahl; J.-P. Herrmann; A. Temming (Marine Biology, 2013)

Bioaccumulation of Selenium by the Bryophyte Hygrohypnum ochraceum in the Fountain Creek Watershed, Colorado - S. J. Herrmann; J. A. Turner; J. S. Carsella; D. W. Lehmpuhl; D. R. Nimmo (Environmental Management, 2012)

Biogas Production from Maize: Current State, Challenges, and Prospects. 1. Methane Yield Potential - A. Herrmann; J. Rath (BioEnergy Research, 2012)

Variants of guided self-organization for robot control - Georg Martius; J. Michael Herrmann (Theory in Biosciences, 2012)

Modification of caffeine effects on the affect-modulated startle by neuropeptide S receptor gene variation - Katharina Domschke; Benedikt Klauke; Bernward Winter; Agnes Gajewska; Martin J. Herrmann; Bodo Warrings; Andreas Mühlberger; Katherina Wosnitza; Andrea Dlugos; Swantje Naunin; Kathrin Nienhaus; Manfred Fobker; et al. (Psychopharmacology, 2012)

Effects of habitat isolation and predation pressure on an arboreal food-web - J. Herrmann; U. Kormann; C. Schüepp; Y. Stocker; F. Herzog; M. Entling (Community Ecology, 2012)

Modified light use efficiency model for assessment of carbon sequestration in grasslands of Kazakhstan: combining ground biomass data and remote-sensing - Pavel A. Propastin; Martin W. Kappas; Stefanie M. Herrmann; Compton J. Tucker (International Journal of Remote Sensing, 2012)

Multi locus analysis of Pristionchus pacificus on La Réunion Island reveals an evolutionary history shaped by multiple introductions, constrained dispersal events and rare out‐crossing - KATY MORGAN; ANGELA McGAUGHRAN; LAURE VILLATE; MATTHIAS HERRMANN; HANH WITTE; GABI BARTELMES; JACQUES ROCHAT; RALF J. SOMMER (Molecular Ecology, 2012)
Pristionchus pacificus, recently established as a model organism in evolutionary biology, is a cosmopolitan nematode that has a necromenic association with scarab beetles. The diverse array of host beetle species and habitat types occupied by P. pacificus make it a good model for investigating local adaptation to novel environments. Presence of P. pacificus on La Réunion Island, a young volcanic island with a dynamic geological history and a wide variety of ecozones, facilitates such investigation in an island biogeographic setting. Microsatellite data from 20 markers and 223 strains and mitochondrial sequence data from 272 strains reveal rich genetic diversity among La Réunion P. pacificus isolates, shaped by differentially timed introductions from diverse sources and in association with different beetle species. Distinctions between volcanic zones and between arid western and wet eastern climatic zones have likely limited westward dispersal of recently colonized lineages and maintained a genetic distinction between eastern and western clades. The highly selfing lifestyle of P. pacificus contributes to the strong fine‐scale population structure detected, with each beetle host harbouring strongly differentiated assemblages of strains. Periodic out‐crossing generates admixture between genetically diverse lineages, creating a diverse array of allelic combinations likely to increase the evolutionary potential of the species and facilitate adaptation to local environments and beetle hosts.

Resurrecting an extinct species: archival DNA, taxonomy, and conservation of the Vegas Valley leopard frog - Evon R. Hekkala; Raymond A. Saumure; Jef R. Jaeger; Hans-Werner Herrmann; Michael J. Sredl; David F. Bradford; Danielle Drabeck; Michael J. Blum (Conservation Genetics, 2011)

Compositionality of arm movements can be realized by propagating synchrony - Alexander Hanuschkin; J. Michael Herrmann; Abigail Morrison; Markus Diesmann (Journal of Computational Neuroscience, 2011)

Sex differences in cognitive control are associated with midcingulate and callosal morphology - Rene J. Huster; R. Westerhausen; C. S. Herrmann (Brain Structure and Function, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Obesity is associated with improved survival in patients with organ-confined clear-cell kidney cancer - Sandra Waalkes; Axel S. Merseburger; Mario W. Kramer; Thomas R. W. Herrmann; Gerd Wegener; Julia Rustemeier; Rainer Hofmann; Mark Schrader; Markus A. Kuczyk; Andres J. Schrader (Cancer Causes & Control, 2010)

SWIR-based spectral indices for assessing nitrogen content in potato fields - I. Herrmann; A. Karnieli; D. J. Bonfil; Y. Cohen; V. Alchanatis (International Journal of Remote Sensing, 2010)

Female-biased incubation and strong diel sex-roles in the Two-banded Plover Charadrius falklandicus - James J. H. St Clair; Philipp Herrmann; Robin W. Woods; Tamás Székely (Journal of Ornithology, 2010)

Effects of temperature and body mass on metabolic rates of sprat, Sprattus sprattus L. - L. Meskendahl; J.-P. Herrmann; A. Temming (Marine Biology, 2010)

Thermodynamic properties of sea air - R. Feistel; D. G. Wright; H.-J. Kretzschmar; E. Hagen; S. Herrmann; R. Span (Ocean Science, 2010)
Very accurate thermodynamic potential functions are available for fluid water, ice, seawater and humid air covering wide ranges of temperature and pressure conditions. They permit the consistent computation of all equilibrium properties as, for example, required for coupled atmosphere-ocean models or the analysis of observational or experimental data. With the exception of humid air, these potential functions are already formulated as international standards released by the International Association for the Properties of Water and Steam (IAPWS), and have been adopted in 2009 for oceanography by IOC/UNESCO. In this paper, we derive a collection of formulas for important quantities expressed in terms of the thermodynamic potentials, valid for typical phase transitions and composite systems of humid air and water/ice/seawater. Particular attention is given to equilibria between seawater and humid air, referred to as "sea air" here. In a related initiative, these formulas will soon be implemented in a source-code library for easy practical use. The library is primarily aimed at oceanographic applications but will be relevant to air-sea interaction and meteorology as well. The formulas provided are valid for any consistent set of suitable thermodynamic potential functions. Here we adopt potential functions from previous publications in which they are constructed from theoretical laws and empirical data; they are briefly summarized in the appendix. The formulas make use of the full accuracy of these thermodynamic potentials, without additional approximations or empirical coefficients. They are expressed in the temperature scale ITS-90 and the 2008 Reference-Composition Salinity Scale.

Effect of temperature on the gastric evacuation in sprat Sprattus sprattus - M. Bernreuther; A. Temming; J.‐P. Herrmann (Journal of Fish Biology, 2009)
Gastric evacuation of groups of juvenile (mean 63 mm total length, L T , 0·283 g dry mass, M D ) sprat Sprattus sprattus feeding on brine shrimp Artemia sp. nauplii was studied at six temperatures (7·5, 10, 13, 16, 19·5 and 21·5° C) in the laboratory. Gastric evacuation was best described with a general model: , with S t = stomach content at time t , S 0 = stomach content at time 0, t = time , R , B = constants. The shape parameter was estimated as B = 0·668. For comparison with other studies, an exponential model was fitted also to the data. The evacuation constant ( R ) of the general gastric evacuation model increased exponentially with temperature between 7·5 and 16° C. The slope of the increase was reduced between 16 and 19·5° C and a slight decrease was observed between 19 and 21·5° C. Additionally, the effect of mean M D (range 0·286 – 1·025 g) was examined. A simple power function ( ) described the influence of predator mass on exponential evacuation constant with C = 0·503. The results of this investigation were integrated into a consumption model for the calculation of daily rations of S. sprattus : , with T = ambient temperature (°C) and of field stomach contents (g dry) individually raised to the power of 0·668.

A neurocomputational model for optimal temporal processing - Joachim Haß; Stefan Blaschke; Thomas Rammsayer; J. Michael Herrmann (Journal of Computational Neuroscience, 2008)

Symmetries, non-Euclidean metrics, and patterns in a Swift–Hohenberg model of the visual cortex - N. Michael Mayer; Matthew Browne; J. Michael Herrmann; Minoru Asada (Biological Cybernetics, 2008)

Secondary structure and distribution of fusogenic LV-peptides in lipid membranes - J. Ollesch; B. C. Poschner; J. Nikolaus; M. W. Hofmann; A. Herrmann; K. Gerwert; D. Langosch (European Biophysics Journal, 2008)

Evolution of the Peak Hill high-sulfidation epithermal Au–Cu deposit, eastern Australia - Richard J. Squire; Walter Herrmann; Daniel Pape; D. Ian Chalmers (Mineralium Deposita, 2007)

Molecular diagnosis of pulmonary tuberculosis by automated extraction and real-time PCR on non-decontaminated pulmonary specimens - V. Drouillon; P. H. Lagrange; J.-L. Herrmann (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Distinct patterns of genetic variation in Pristionchus pacificus and Caenorhabditis elegans , two partially selfing nematodes with cosmopolitan distribution - HANS ZAUNER; WERNER E. MAYER; MATTHIAS HERRMANN; ANDREAS WELLER; MIRJA ERWIG; RALF J. SOMMER (Molecular Ecology, 2007)
Hermaphroditism has evolved several times independently in nematodes. The model organism Caenorhabditis elegans and Pristionchus pacificus are self‐fertile hermaphrodites with rare facultative males. Both species are members of different families: C. elegans belongs to the Rhabditidae and P. pacificus to the Diplogastridae. Also, both species differ in their ecology: C. elegans is a soil‐dwelling nematode that is often found in compost heaps. In contrast, field studies in Europe and North America indicate that Pristionchus nematodes are closely associated with scarab beetles. In C. elegans, several recent studies have found low genetic diversity and rare out‐crossing events. Little is known about diversity levels and population structure in free‐living hermaphroditic nematodes outside the genus Caenorhabditis . Taking a comparative approach, we analyse patterns of molecular diversity and linkage disequilibrium in 18 strains of P. pacificus from eight countries and four continents. Mitochondrial sequence data of P. pacificus isolates reveal a substantially higher genetic diversity on a global scale when compared to C. elegans . A mitochondrial‐derived hermaphrodite phylogeny shows little geographic structuring, indicating several worldwide dispersal events. Amplified fragment length polymorphism and single strand conformation polymorphism analyses demonstrate a high degree of genome‐wide linkage disequilibrium, which also extends to the mitochondrial genome. Together, these findings indicate distinct patterns of genetic variation of the two species. The low level of genetic diversity observed in C. elegans might reflect a recent human‐associated dispersal, whereas the P. pacificus diversity might reflect a long‐lasting and ongoing insect association. Thus, despite similar lifestyle characteristics in the laboratory, the reproductive mode of hermaphroditism with rare facultative males can result in distinct genetic variability patterns in different ecological settings.

Inheritance and mapping of a powdery mildew resistance gene introgressed from Avena macrostachya in cultivated oat - J. Yu; M. Herrmann (Theoretical and Applied Genetics, 2006)

Source Localization of Early Stages of Face Processing - Martin J. Herrmann; Ann-Christine Ehlis; Andreas Muehlberger; Andreas J. Fallgatter (Brain Topography, 2005)

Calcium Tartrate Crystals in the Midgut of the Grape Leafhopper - S. Böll; T. Schmitt; C. Burschka; P. Schreier; P. Schwappach; J. V. Herrmann (Journal of Chemical Ecology, 2005)

Induction of apoptosis by spermine-metabolites in primary human blood cells and various tumor cell lines - M. Schiller; N. Blank; P. Heyder; M. Herrmann; U. S. Gaipl; J. R. Kalden; H. M. Lorenz (Apoptosis, 2005)

Ontogenic changes in the allometric scaling of the mass and length relationship in Sprattus sprattus - M. A. Peck; C. Clemmesen; J.‐P. Herrmann (Journal of Fish Biology, 2005)
An analysis of mass ( M ) and standard length ( L S ) data for larval, juvenile and adult sprat ( Sprattus sprattus ; Clupeidae) revealed marked changes in the allometric scaling factor ( b in ). For sprat L S , b was 5·0, whereas in larger juveniles and adults, b was c. 3·4 indicating a relatively protracted metamorphic period for this species.

Comparative analysis of adenoviral transgene delivery via tail or portal vein into rat liver - J. Herrmann; B. Abriss; E. van de Leur; S. Weiskirchen; A. M. Gressner; R. Weiskirchen (Archives of Virology, 2004)

A simplified method for monitoring eggs of the grape leafhopper (Empoasca vitis) in grapevine leaves - J. V. Herrmann; Susanne Böll (Journal of Plant Diseases and Protection, 2004)

A long-term study on the population dynamics of the grape leafhopper ( Empoasca vitis ) and antagonistic mymarid species - S. Bll; J. V. Herrmann (Journal of Pest Science, 2004)

Shaping of Receptive Fields in the Visual Cortex During Retinal Maturation - Norbert Mayer; J. Michael Herrmann; Theo Geisel (Journal of Computational Neuroscience, 2003)

Effects of selective inactivation of individual genes for low-molecular-mass subunits on the assembly of photosystem II, as revealed by chloroplast transformation: the psbEFLJ operon in Nicotiana tabacum - M. Swiatek; R. E. Regel; J. Meurer; G. Wanner; H. B. Pakrasi; I. Ohad; R. G. Herrmann (Molecular Genetics and Genomics, 2003)

Photocatalytic degradation of the herbicide cinosulfuron in aqueous TiO 2 suspension - E. Vulliet; C. Emmelin; J.-M. Chovelon; C. Guillard; J.-M. Herrmann (Environmental Chemistry Letters, 2003)

Treatment of Severe Candida Infections in High-Risk Patients in Germany: Consensus Formed by a Panel of Interdisciplinary Investigators - Büchner T.; Fegeler W.; Bernhardt H.; Brockmeyer N.; Duswald K.-H.; Herrmann M.; Heuser D.; Jehn U.; Just-Nübling G.; Karthaus M.; Maschmeyer G.; Müller F.-M.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Dynamical systems for predictive control of autonomous robots - J. Michael Herrmann (Theory in Biosciences, 2001)

N budget and NH3 exchange of a grass/clover crop at two levels of N application - B. Herrmann; S. K. Jones; J. Fuhrer; U. Feller; A. Neftel (Plant and Soil, 2001)

P300 and LORETA: Comparison of Normal Subjects and Schizophrenic Patients - G. Winterer; C. Mulert; S. Mientus; J. Gallinat; P. Schlattmann; H. Dorn; W.M. Herrmann (Brain Topography, 2001)

Gastric evacuation in horse mackerel. I. The effects of meal size, temperature and predator weight - A. Temming; J.‐P. Herrmann (Journal of Fish Biology, 2001)
Gastric evacuation experiments were performed on horse mackerel Trachurus trachurus. A nearly full matrix experimental design with respect to the variables predator weight ( Osmerus eperlanus as prey. A general evacuation model without meal size as a variable was fitted to the data on wet weights as well as on dry weights by means of non‐linear regression technique. Two methods of data transformation, relative data and square root transformation, were applied to improve variance homogeneity. The most reliable model fit was achieved on dry weight data applying the square root transformation technique: image where S t =stomach content (g wet weight) at time t after ingestion, S 0 =the initial meal size, W =predator (g wet weight), and T =temperature. The estimated coefficient of the exponential temperature function, δ=00·032, corresponds to a Q 10 value of 1·4 which is outstandingly low in comparison with results on other species. However additional experiments to determine maximum daily food rations indicated that appetite in contrast to gastric evacuation is strongly temperature dependent.

Gastric evacuation of horse mackerel. II. The effects of different prey types on the evacuation model - A. Temming; J.‐P Herrmann (Journal of Fish Biology, 2001)
Gastric evacuation experiments were performed on horse mackerel Trachurus trachurus. Discrete meals of different sizes of krill Meganyctiphanes norvegicus, mysids Neomysis integer , brown shrimp Crangon crangon , and herring Clupea harengus were fed to test the effect of prey type on the gastric evacuation. A general evacuation model without meal size as a variable was fitted to the data on dry weights by means of non‐linear regression. With the exception of mysid evacuation the estimated parameters for curvature, predator weight effect, and temperature effect of the general evacuation model were very similar for all other food types and also confirmed the results obtained with smelt Osmerus eperlanus. In contrast the evacuation of mysids showed a strong exponential curvature, rather the effect of prey size than of prey type. The prey specific evacuation constants of the model revealed a linear relationship to the energy content. A general consumption model for field estimates is presented that can be used for prey types that have not yet been tested in the experiments, provided the energy content is known.

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Role of apoptosis in autoimmunity - H-M. Lorenz; M. Herrmann; T. Winkler; U. Gaipl; J. R. Kalden (Apoptosis, 2000)

Human astrovirus isolation and propagation in multiple cell lines - J. P. Brinker; N. R. Blacklow; J. E. Herrmann (Archives of Virology, 2000)

Effect of body size on the standard metabolism of horse mackerel - J‐P. Herrmann; E. C. Enders (Journal of Fish Biology, 2000)
The routine metabolic rate R R and standard metabolic rate R S were measured in horse mackerel Trachurus trachurus at 13°C over weight range of 1·4–390 g. A data extraction method rather than the more commonly used method of extrapolating the swimming speed‐metabolic rate curves back to zero swimming speed was developed to measure the R S . The relation between R R and R S and weight was expressed as a linear regression with the log transformed data. The mean slope of the regression was 0·752 for R S and 0·725 for R S .

Stability of Late Event-Related Potentials: Topographical Descriptors of Motor Control Compared with the P300 Amplitude - Andreas J. Fallgatter; Sabine S. Eisenack; Barbara Neuhauser; Derlis Aranda; Peter Scheuerpflug; Martin J. Herrmann (Brain Topography, 2000)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Proving the Authenticity of Ancient DNA by Comparative Genomic Hybridization - S. Hummel; B. Herrmann; J. Rameckers; D. Müller; K. Sperling; H. Neitzel; H. Tönnies (The Science of Nature, 1999)

The mouse Rsk3 gene maps to the Leh66 elements carrying the t -complex responder Tcr - Andreas Kispert; Reinhard J. Stöger; Marta Caparros; Bernhard G. Herrmann (Mammalian Genome, 1999)

Physical mapping and molecular-cytogenetic analysis of substitutions and translocations involving chromosome 1D in synthetic hexaploid triticale - U. Hohmann; J. Zoller; R. G. Herrmann; M. E. Kazman (Theoretical and Applied Genetics, 1999)

Diurnal changes in xylem pressure and mesophyll cell turgor pressure of the lianaTetrastigma voinierianum: The role of cell turgor in long-distance water transport - F. Thrmer; J. J. Zhu; N. Gierlinger; H. Schneider; R. Benkert; P. Gener; B. Herrmann; F. -W. Bentrup; U. Zimmerniann (Protoplasma, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

UV-B Irradiated Cell Lines Execute Programmed Cell Death in Various Forms - M. Hagenhofer; H. Germaier; C. Hohenadl; P. Rohwer; J. R. Kalden; M. Herrmann (Apoptosis, 1998)

Biophysical characterization of the interaction of bovine seminal plasma protein PDC-109 with phospholipid vesicles - Peter Müller; Karl-Rudolf Erlemann; Karin Müller; Juan J. Calvete; Edda Töpfer-Petersen; Kathleen Marienfeld; A. Herrmann (European Biophysics Journal, 1998)

Lateral Variations of Lg Coda Q in Southern Mexico - J. Yamamoto; L. Quintanar; R.B. Herrmann; C. Fuentes (Pure and Applied Geophysics, 1997)

Immunological characterization of the Marin County strain of astrovirus - J. E. Herrmann; W. D. Cubitt; R. W. Hudson; Dorothy M. Perron-Henry; L. S. Oshiro; N. R. Blacklow (Archives of Virology, 1990)

Plaque quantitation and virus neutralization assays for human astroviruses - R. W. Hudson; J. E. Herrmann; N. R. Blacklow (Archives of Virology, 1989)

Preparation and characterization of monoclonal antibodies to enteric adenovirus types 40 and 41 - J. E. Herrmann; Dorothy M. Perron-Henry; Darlene Stobbs-Walro; N. R. Blacklow (Archives of Virology, 1987)

Zur Pyruvat- und ?-Ketoglutaratausscheidung durch Streptomyces rimosus - E.-J. Bormann; R. Herrmann (Archives of Microbiology, 1968)